A 6-Year Posttreatment Follow-up of Panic Disorder Patients: Treatment With Clonazepam Predicts Lower Recurrence Than Treatment With Paroxetine. Issue 4 (August 2017) - Freire, Rafael C.; Amrein, Roman; Mochcovitch, Marina D.; Dias, Gisele P.; Machado, Sergio; Versiani, Marcio; Arias-Carrión, Oscar; Carta, Mauro G.; Nardi, Antonio E.
Abstract: Background: The aim of this study was to identify factors associated with relapse in panic disorder (PD). Methods: This was an observational study conducted in the outpatient clinic of a psychiatric hospital in Rio de Janeiro, Brazil. In a previous study, 120 patients diagnosed as having PD according to Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition criteria were randomized to receive clonazepam or paroxetine. After 3 years, treatment was discontinued in patients who had achieved remission. These subjects were included in the current study and were followed up for 6 years. The follow-up assessments were made at 1, 2, 3, 5, and 6 years after treatment discontinuation. Assessment included the number of panic attacks per month, Clinical Global Impression–Severity, and other measures. Patients who had initiated psychotherapy or pharmacological treatment because of PD symptoms or who had Clinical Global Impression–Severity scores greater than 1 or panic attacks in the month preceding the assessment were considered relapse cases. Data were collected from January 2003 to August 2012. Results: Eighty-five patients completed the follow-up. Cumulative relapse rates were 50% (n = 33) at 1 year and 89.4% (n = 76) at 6 years. One-year relapse rates were lower in patients previously treated with clonazepam ( P = 0.001) compared with those treated with paroxetine. Low 6-year relapse rates were associated with high Hamilton Anxiety Rating Scale scores before treatment ( P = 0.016) and previous treatment with clonazepam. Conclusions: Relapse is a frequent problem in PD, and long-term treatment does not protect these patients in the long run. Treatment with clonazepam predicts lower relapse when compared with paroxetine.